Carrier mobility and trap distribution dependent flashover characteristics of epoxy resin. Issue 2 (1st November 2017) - Du, Boxue; Du, Qiang; Li, Jin; Liang, Hucheng
Abstract : Epoxy disc‐type spacer, as the major insulator of gas insulated transmission line, plays a significant role in the reliability and safety of the entire power grid. While surface charge accumulation on the spacer could induce flashover and accelerate degradation of the insulator, which threats the operation of high‐voltage DC transmission and grid. In this study, a corona discharging system was employed to charge the epoxy samples before the charge dissipation measured, and the surface flashover voltages of samples with different modification time under DC voltage were also measured, the results are obtained from the research. It is found that the carrier mobility and surface flashover voltage of samples are affected by modification time, and maximum value of both can be obtained when the sample is modified for 60 min. Under the combined voltages, the initial surface charge density and carrier mobility are affected by both pulse voltage and modification time. It is indicated that surface modification is an appropriate method which can significantly inhibit the surface charge accumulation, and improve the flashover characteristics of epoxy sample by increasing carrier mobility. The trap distribution characteristics suggested that the modification treatment and charging condition have a significant effect on the depth and density of trap.